2017
DOI: 10.1021/acs.jpcc.6b11528
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrocatalytic Performance of Pt3Pd1 Alloys Supported on CeO2/C for Methanol Oxidation and Oxygen Reduction Reactions

Abstract: Direct methanol fuel cell (DMFC) with noble metals based anode and cathode is a promising energy generator to portable power devices. However, the deterioration of catalyst performance suffered by CO poisoning, crossover of fuel from anode to cathode, and higher economical cost of such devices hinder their commercialization. Herein, all of the above issues have been neutralized and crossed the huge hump of faced challenges. Highly efficient, durable, and surfactant-free catalyst with ultralow Pt3Pd1 loadings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 54 publications
(77 reference statements)
0
40
0
Order By: Relevance
“…[17][18][19][20][21][22][23][24][25] For instance, compared to their constituents, bimetallic PdÀ Pt nanomaterials can offer improved activity in catalytic applications. [22][23][24][25] Aside the composition, the shape and size of nanostructures represent important factors in determining their properties. In this regard, metal nanotubes (NTs) as one-dimensional, hollow nanoobjects frequently outperform more conventional morphologies, such as nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25] For instance, compared to their constituents, bimetallic PdÀ Pt nanomaterials can offer improved activity in catalytic applications. [22][23][24][25] Aside the composition, the shape and size of nanostructures represent important factors in determining their properties. In this regard, metal nanotubes (NTs) as one-dimensional, hollow nanoobjects frequently outperform more conventional morphologies, such as nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies have found that many metals have catalytic properties for methanol oxidation, which has attracted great interest, such as Sn, Cu, Ni, Mo, etc. In recent years, many researchers have been working on the application of platinum‐based bimetallic alloy catalysts in DMFCs, such as Pt–Pd, Pt–Ag, Pt–Ru, Pt–Fe, Pt–Sn, Pt–Au, Pt–Co, Pt–Ni and Pt–Mo . The results show that these alloy catalysts have good effect on the decomposition and oxidation of methanol, while reducing the cost of raw materials and improving the tolerance towards CO poisoning .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Yousaf et al have investigated the electrocatalytic performance of Pt and Pd alloys for methanol oxidation reactions and ORR. 11,12 However, platinum and its alloys have disadvantages, such as high cost, scarce resources and inferior durability, that impede their widespread commercialization and limit their performance. 1,8 Therefore, there is an urgent need to search for new cheap metal or metal-free catalysts with unexceptionable electrocatalytic properties for ORRs.…”
Section: Introductionmentioning
confidence: 99%